HPLC Deternation of Telsartan in Bulk and Pharmaceutical Formulations - Nageswara Rao, R.; Sen, S.; Nagaraju, P.; Sumanth Reddy, V.; Radha Krishnamurthy, P.; Uday Bhaskar, S. (Asian Journal of Chemistry, 2010)
A rapid and sensitive high performance liquid chromatographic method was developed for the estimation of telsartan in pharmaceutical dosage forms. Telsartan was chromatographed on a reverse phase C18 column in a mobile phase consisting of methanol : acetonitrile : buffer (pH 2.8) in the ratio of 20 : 70 : 10 v/v. The mobile phase was pumped at a flow rate of 1 mL/n and the eluents were monitored at 290 nm. The calibration curve was linear in the range of 10–1000 ng/mL. The intra- and inter-day variation was found to be less than 1% showing high precision of the assay method. The mean recovery of the drug from the solution containing 50 ng/mL was 96.6 ± 1.13% indicating high accuracy of the proposed HPLC method. Due to its simplicity, rapidness, high precision and accuracy the proposed HPLC method may be used for deterning telsartan in bulk drug samples and pharmaceutical dosage forms.